Is Your Product Really Green? A Content Analysis to Reassess Green Advertising. Issue 1 (2nd January 2016) - Segev, Sigal; Fernandes, Juliana; Hong, Cheng
Abstract : This article investigates the changes in green advertising by conceptually replicating and extending Carlson, Grove, and Kangun's 1993 study. A content analysis of 433 unique ads from 18 magazine titles published in 2009 and 2010 demonstrates that advertisers attempted to address growing public concern for the environment and the demand for green products and services as emerge from the analyses of the ads' target, objective, and the executional elements. Contrary to Carlson, Grove, and Kangun's findings, the majority of environmental claims were deemed acceptable, implying a trend toward more trustworthy and reliable green advertising.